2021
DOI: 10.1038/s41598-021-99189-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-enhanced reduced graphene oxide photodetector with monometallic of Au and Ag nanoparticles at VIS–NIR region

Abstract: Hybrids plasmonic nanoparticles (NPs) and unique 2D graphene significantly enhanced the photoresponse of the photodetectors. The metallic NPs that exhibit localized surface plasmon resonance (LSPR) improves strong light absorption, scattering and localized electromagnetic field by the incident photons depending on the optimum condition of NPs. We report high-performance photodetectors based on reduced graphene oxide (rGO) integrated with monometallic of Au and Ag nanoparticles via a familiar fabrication techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…However, for monolayer 2D photodetectors, their overall photoresponsivity and detectivity are relatively low due to the limited optical absorption cross-section for atomic thickness. Hence, integrating metal nanoparticle arrays has been demonstrated as an effective approach for enhancing their optoelectronic properties, due to the plasmonic coupling effect of nanoparticles. Within our approach, the coshell Ag nanoparticles are simultaneously realized (as a byproduct) during the dry-exfoliation step of the MoS 2 monolayer, which could be further used for high-performance photodetection without complex approaches for nanoparticle synthesis and integration.…”
Section: Resultsmentioning
confidence: 99%
“…However, for monolayer 2D photodetectors, their overall photoresponsivity and detectivity are relatively low due to the limited optical absorption cross-section for atomic thickness. Hence, integrating metal nanoparticle arrays has been demonstrated as an effective approach for enhancing their optoelectronic properties, due to the plasmonic coupling effect of nanoparticles. Within our approach, the coshell Ag nanoparticles are simultaneously realized (as a byproduct) during the dry-exfoliation step of the MoS 2 monolayer, which could be further used for high-performance photodetection without complex approaches for nanoparticle synthesis and integration.…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, the following three issues should be settled in the first place to accelerate the development of plasmon-induced hot carrier applications. [361] WS 2 ∕Au NPs Au NPs 1050 at 590 nm -Liu 2019 [363] CdTe nanowire/Au NPs Au NPs 2.26 × 10 4 at 826 nm 12.5 Luo 2014 [364] Ag/graphene oxide Ag NPs 17.23 at 785 nm 7.17 Rohizat 2021 [365] Ag/ZnSe nanowire Ag NPs 0.1848 at 480 nm 9.2 Wang 2016 [366] Au/ZnTe nanowire Au NPs 5.11 × 10 3 at 539 nm 328 Luo 2016 [367] Hollow Au NPs∕Bi 2 S 3 nanowire Au NPs 1.09 × 10 3 at 953 nm 278 Liang 2017 [368] ITO/Ge nanoneedles ITO NPs 0.185 at 1550 nm 228 Lu 2016 [369] Fig. 20 (a) Transient linear dichroism of a metasurface consisting of a lattice of Au symmetric nanocrosses.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, noble metal nanoparticles (NPs) are extensively explored as an active element for the hybrid PD component as they can provide strong absorption, scatting, and local e-field enhancement via localized surface plasmonic resonance (LSPR). , To date, Ag and Au NPs have been widely explored in a variety of optical applications due to their intense dipolar and quadrupolar resonance modes in the collective oscillation, which can effectively generate hot electrons in the vicinity of NPs . For example, Nurul et al reported the ultrahigh responsivity of 17.23 A/W in an Ag-incorporated rGO photodetector . Gogurla et al demonstrated an Au NPs/ZnO composite for UV photodetection with 80 times enhancement over ZnO .…”
Section: Introductionmentioning
confidence: 99%